Humanitarian intervention and international relations - Welsh, Jennifer M. (Jennifer Mary) 1965-. (Oxford Oxford University Press, 2004)
The issue of humanitarian intervention has generated one of the most heated debates in international relations since 1990 - among both theorists and practitioners. This volume investigates the controversial place of humanitarian intervention in the theory and practice of international relations.
Keywords: Humanitarian intervention; International relations